Dermatology Life Quality Index as a Prognostic Tool for Predicting Need for Healthcare in Patients with Eczema: A Pilot Study - Wasim Jamil; Laura von Kobyletzki; Mats Berg; Magnus Lindberg (Medical Journals Sweden, 2022)
Abstract is missing (Short Communication)